Choice Architecture to Improve Financial Decision Making - Carpenter, Jeffrey; Huet-Vaughn, Emiliano; Matthews, Peter Hans; Robbett, Andrea; Beckett, Dustin; Jamison, Julian (The Review of Economics and Statistics, 2021)
We exploit the principles of choice architecture to evaluate interventions in the market for reloadable prepaid cards. Participants are randomized into three card menu presentation treatments—the market status quo, a regulation-inspired reform, or an enhanced reform designed to minimize attribute overload—and offered choices based on prior structural estimation of individual preferences. Consumers routinely choose incorrectly under the status quo, with tentative evidence that the regulation-inspired presentation may increase best card choice and clear evidence that the enhanced reform reduces worst card choice. Welfare analysis suggests the regulation-inspired presentation offers modest gains, while the enhanced policy generates substantial benefits.